Enhancing immunotherapy response in melanoma: myeloid-derived suppressor cells as a therapeutic target - Özbay Kurt, Feyza Gül; Lasser, Samantha; Arkhypov, Ihor; Utikal, Jochen; Umansky, Viktor (The journal of clinical investigation, 2023)
Despite the remarkable success of immune checkpoint inhibitors (ICIs) in melanoma treatment, resistance to them remains a substantial clinical challenge. Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population of myeloid cells that can suppress antitumor immune responses mediated by T and natural killer cells and promote tumor growth. They are major contributors to ICI resistance and play a crucial role in creating an immunosuppressive tumor microenvironment. Therefore, targeting MDSCs is considered a promising strategy to improve the therapeutic efficacy of ICIs. This Review describes the mechanism of MDSC-mediated immune suppression, preclinical and clinical studies on MDSC targeting, and potential strategies for inhibiting MDSC functions to improve melanoma immunotherapy.
Veröffentlicht: 3. Juli 2023
Gesehen am 28.09.2023